A case of crescentic glomerulonephritis with exacerbation of pre-existing IgA nephropathy after COVID-19 - Karabağ Yılmaz, Esra; Saygılı, Seha; Musayeva, Gülüstan; Gülmez, Rüveyda; Ağbaş, Ayşe; Özlük, Yasemin; Canpolat, Nur (The Turkish Journal of Pediatrics, 2024)
Background. Relapses or new-onset IgA nephropathy (IgAN) have been documented in patients after vaccination against SARS-CoV-2; however, only one adult patient has been reported in whom pre-existing IgAN worsened during coronavirus disease 2019 (COVID-19). Case. We present the first pediatric case with biopsy-proven IgAN and genetically confirmed Alport syndrome, who developed end-stage kidney disease after an exacerbation of IgAN associated with COVID-19. The patient’s basal serum creatinine was 0.7-0.9 mg/dL before infection. He had not been vaccinated against COVID-19. He was admitted to the hospital with edema, hypertension, an elevated serum creatinine of 4.7 mg/dL, and massive proteinuria. Three months before admission, he had been admitted to another hospital with COVID -19 and an elevated serum creatinine (1.9 mg/dL), but no biopsy had been performed at that time. The kidney biopsy revealed IgAN with 50% fibrocellular crescents with sclerosed glomeruli, tubular atrophy, and interstitial fibrosis. His serum creatinine did not decrease even after five administrations of pulse steroids, and hemodialysis was initiated. Conclusion. In conclusion, COVID -19 may pose a high risk for exacerbation of pre-existing glomerular disease. It is therefore necessary to closely monitor the kidney function of patients with underlying glomerulonephritis during and after COVID-19 and consider an early biopsy if serum creatinine does not return to baseline levels. In addition, this case report highlights the clinical importance of the co-occurence of IgAN and Alport syndrome.